Poverty within the watershed and environmeantally protected areas (wepa): The case of the indigenous community (Orang Asli) in Malaysia - Fatimah, K.; Siti Hajar, Y. (2014)
The Indigenous People (Orang Asli) are a heterogeneous community scattered over more than 850 villages in Peninsular Malaysia. While 60 percent are located in the outskirts of existing rural villages, 37 percent live in remote areas, and a very small number reside in the vicinity of existing township. The Orang Asli population has been identified to be among the poorest and the most socio-economically and culturally marginalized in Peninsular Malaysia. This paper attempts to build a simple behavioral model topredict and explain the multi-faceted factors in contributing towards their poverty, especially among the Orang Asli community living within the watershed and environmental protected areas. The preliminary finding shows that the Orang Asli community is quite likely to be poor if they settled in environmental sensitive and protected areas as compared to families under the new resettlement scheme. Access to basic education and employment contributed significantly to the poor economic status of the Orang Asli. Our preliminary findings show that the poor households among Orang Asli faced some difficulty in getting access and support in terms of basic needs such as housing, education, economic livelihood and other social infrastructure. More importantly, the government regulatory structure in terms of managing watershed areas and agricultural land for commodity crops has indirectly . contributed towards the poverty levels of the Orang Asli. As such, Orang Asli community linkages with land ownership remain to be an important factor in affecting their-livelihood in the rural remote and isolated areas.